Liquid–liquid phase equilibrium of methanol + ethylbenzene + isooctane + ethanol system at 303 K - Gramajo, Monica Beatriz (2017)
The phase equilibrium data for methanol + ethanol + isooctane systems were obtained at 303.15 K. Data for methanol + ethylbenzene + isooctane system were taken from literature. The effect of ethanol addition on the system equilibrium was investigated at the same temperature. The distribution curves for ternary and quaternary system was analyzed. The experimental results for ternary systems were correlated with UNIQUAC and NRTL equations. For the ternary systems studied here, the NRTL equation is more accurate than the UNIQUAC. The equilibrium data for the three ternary systems were used to determine interactions parameters for the UNIQUAC equation. For the quaternary system, the experimental data can be fitted more accurately to UNIQUAC equation than by the UNIFAC method.